Կրօնի և գիտութեան հակամարտութեան հիմնախնդրի շուրջ - Յակոբեան, Գէորգ (Տպարան Սրբոյ Յակոբեանց)
Յոդվածում քննարկվում է կրօնի և գիտութեան ռացիոնալ համակարտութեան լիգիտիմութեան հարցը: The article deals with the problem of the rational legitimacy of the conflict between religion and science.
Keywords: Philosophy; Psychology; Religion; Science; Religion